(untitled) (Bioresearch Communications, 2023)
An attempt has been made for molecular characterization of gastropods from three different ecological habitats (marine, freshwater and terrestrial) in Bangladesh. A total of eight species of gastropod (Lissachatina fulica, Pila globosa, Pila virens, Brotia costula, Nerita articulata, Nerita balteata, Macrochlamys indica and Telescopium telescopium) were identified belongs to seven genera and six families. These species were confirmed through morphological studies and by adopting DNA barcoding using mitochondrial cytochrome c oxidase subunit I (COI) and 16S ribosomal RNA (16S rRNA) gene. The average GC content 39.53% and 33.40% were found for COI and 16S rRNA, respectively. Genetic divergence increased as predicted with higher taxonomic rank, ranging from 0% to 2.84% with an average 1.45% within species and 3.57% to 35.23% between species with a DNA barcoding gap of 0.73 for 16S. This study revealed that gastropod species can be discriminated using both COI and 16S rRNA gene. Phylogenetic relationships among identified species were established where individuals belonging to the same species were grouped under the same clade. Molecular characterization of remaining molluscan species of Bangladesh remains to be completed. Bioresearch Commu. 9(2): 1305-1309, 2023 (July)